1997
DOI: 10.1111/j.1745-6584.1997.tb00077.x
|View full text |Cite
|
Sign up to set email alerts
|

Geoelectrical and Hydrogeochemical Studies for Delineating Ground‐Water Contamination Due to Salt‐Water Intrusion in the Northern Part of the Nile Delta, Egypt

Abstract: A resistivity survey was conducted in the Nile Delta area to delineate ground‐water contamination caused by an improper sewage and irrigation drainage system, leaching from old lagoonal deposits, and salt‐water intrusion. Existing monitoring wells were used to measure the horizontal and vertical variations in water salinity. Vertical electrical sounding (VES) data for sounding points located near monitoring wells, together with the water salinity data of these wells, were used to obtain an empirical relationsh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(47 citation statements)
references
References 3 publications
1
43
0
1
Order By: Relevance
“…The correlation was found in geo-electrical study on seawater intrusion (Ebraheem et al 1997;Wilson et al 2006;Sherif et al 2006;Pujari and Soni 2008). Interpretation of resistivity data is difficult, however, for salinity changes that are due to interaction between seawater intrusion and fresh groundwater and to background resistivity; the most challenging is attempting to link earth resistivity to groundwater type (fresh, brackish, or saline).…”
Section: Hydro-geochemical Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…The correlation was found in geo-electrical study on seawater intrusion (Ebraheem et al 1997;Wilson et al 2006;Sherif et al 2006;Pujari and Soni 2008). Interpretation of resistivity data is difficult, however, for salinity changes that are due to interaction between seawater intrusion and fresh groundwater and to background resistivity; the most challenging is attempting to link earth resistivity to groundwater type (fresh, brackish, or saline).…”
Section: Hydro-geochemical Parametersmentioning
confidence: 99%
“…11,12,13,14,15,16,17,18,19,20,21). Ebraheem et al (1997) and Sherif et al (2006) stated that empirical relationship between geochemistry and geophysical methods could be derived when ions dissolved in pore fluid rather than in host soil were more apparent in the electrical images. Findings of early research on use of the empirical relationship as showed by resistivityimage data could be used in this study.…”
Section: Hydro-geochemical Parametersmentioning
confidence: 99%
“…Various researchers are found in the literature, exploiting direct current geoelectrical methods competence in groundwater salinization investigations around the world. Examples of one dimensional soundings include: Urish and Frohlich (1990);Frohlich et al (1994); Ebraheem et al (1997); Nowroozi et al (1999);Choudhury et al (2001); Edet and Okereke (2001); Sherif et al (2006);and Adepelumi et al (2009). In all the aforementioned studies, the authors were able to successfully distinguish between freshwater and saltwater domains in various geological environments, by combining the results of numerous Vertical Electrical Soundings (VES) across coastal zones.…”
Section: Introductionmentioning
confidence: 99%
“…The direct current (DC) resistivity method for conducting a VES is effectively used for groundwater study due to the simplicity of the technique, easy interpretation and the rugged nature of the associated instrumentation. The technique is widely used in soft and hard rock areas and previous study using this technique includes (Ebraheem et al, 1997;Frohlich et al, 1994;Olorunfemi et al, 1999;Adelusi and Balogun, 2001;Omosuyi et al, 2003;Oladapo et al, 2004) The present study is to determine the geoelectric and Dar-Zarrouk parameters in evaluating the groundwater potential and aquifers risk to surface infiltrations.…”
Section: Introductionmentioning
confidence: 99%